Two new species of Trichocomaceae (Eurotiales), accommodated in Rasamsonia and Talaromyces section Bacillispori, from the Czech Republic - Špetík, Milan; Eichmeier, Aleš; Burgová, Jana; Houbraken, Jos (Scientific reports, 2023)
During a previous study on microfungi associated with clematis roots, Penicillium-like fungi were isolated and identified based on morphology. In this study, we subjected those strains to a detailed examination which led to the proposal of two taxonomic novelties, named Rasamsonia chlamydospora and Talaromyces clematidis. The first taxon is characterized by rough-walled mycelium, acerose to flask shaped phialides, cylindrical conidia and by production of chlamydospore-like structures. The four-loci-based phylogeny analysis delineated the taxon as a taxonomic novelty in Rasamsonia. Talaromyces clematidis is characterized by restricted growth on Czapek yeast extract agar, dichloran 18% glycerol agar and yeast extract sucrose agar, and production of yellow ascomata on oatmeal agar. Phylogenetic analyses placed this taxon as a taxonomic novelty in Talaromyces sect. Bacillispori. Both taxa are introduced here with detailed descriptions, photoplates and information on their phylogenetic relationship with related species.
Keywords: Česká republika; Phylogeny; fylogeneze; Eurotiales; Czech Republic; Agar; Talaromyces; agar